Clinical effectiveness of first-line chemoradiation for adult patients with locally advanced non-small cell lung cancer: a systematic review - T Brown (Health Technology Assessment, 2013)
Background: The National Institute for Health and Clinical Excellence has issued guidelines on the treatment of non-small cell lung cancer (NSCLC) and recommends that patients with stage IIIA–IIIB disease who are not amenable to surgery be treated with potentially curative chemoradiation (CTX-RT). This review was conducted as part of a larger systematic review of all first-line chemotherapy (CTX) and CTX-RT treatments for patients with locally advanced or metastatic NSCLC. However, it was considered that patients with potentially curable disease (e.g. stage IIIA) are different from those with advanced disease, who are suitable for palliative treatment only, and therefore the results should be reported separately. Objective: To evaluate the clinical effectiveness of first-line CTX in addition to radiotherapy (RT) (CTX-RT vs CTX-RT) for adult patients with locally advanced NSCLC who are suitable for potentially curative treatment. Data sources: Three electronic databases (MEDLINE, EMBASE and The Cochrane Library) were searched from January 1990 to September 2010. Review methods: Inclusion criteria comprised adult patients with locally advanced NSCLC, trials that compared any first-line CTX-RT therapy (induction, sequential, concurrent and consolidation) and outcomes of overall survival (OS) and/or progression-free survival (PFS). The results of clinical data extraction and quality assessment were summarised in tables and with narrative description. Direct meta-analyses using OS data were undertaken where possible: sequential CTX-RT compared with concurrent CTX-RT; sequential CTX-RT compared with concurrent/consolidation CTX-RT; and sequential CTX-RT compared with concurrent CTX-RT with or without consolidation. There were not sufficient data to perform meta-analysis on PFS. Results: Of the 240 potentially relevant studies that were published post 2000, 19 met the inclusion criteria and compared CTX-RT with CTX-RT. The results from the OS meta-analysis comparing sequential CTX-RT with concurrent CTX-RT appear to show an OS advantage for concurrent CTX-RT arms over sequential arms; this result is not statistically significant [hazard ratio (HR) 0.79; 95% confidence interval (CI) 0.50 to 1.25)]. The results from the OS meta-analysis comparing sequential CTX-RT with concurrent/consolidation CTX-RT appear to show a statistically significant OS advantage for concurrent/consolidation CTX-RT treatment over sequential treatment (HR 0.68; 95% CI 0.55 to 0.83). The results from the OS meta-analysis comparing sequential CTX-RT with concurrent CTX-RT with or without consolidation appear to show a statistically significant OS advantage for concurrent CTX-RT with or without consolidation over sequential treatment (HR 0.72; 95% CI 0.61 to 0.84). Limitations: This report provides a summary and critical appraisal of a comprehensive evidence base of CTX-RT trials; however, it is possible that additional trials have been reported since our last literature search. It is disappointing that the quality of the research in this area does not meet the accepted quality standards regarding trial design and reporting. Conclusions: This review identified that the research conducted in the area of CTX-RT was generally of poor quality and suffered from a lack of reporting of all important clinical findings, including OS. The 19 trials included in the systematic review were too disparate to form any conclusions as to the effectiveness of individual CTX agents or types of RT. The focus of primary research should be good methodological quality; appropriate allocation of concealment and randomisation, and comprehensive reporting of key outcomes, will enable meaningful synthesis and conclusions to be drawn. Funding: The National Institute for Health Research Health Technology Assessment programme.